2017
DOI: 10.5751/ace-01092-120219
|View full text |Cite
|
Sign up to set email alerts
|

No effect of insect abundance on nestling survival or mass for three aerial insectivores

Abstract: ABSTRACT. Swallows, along with other aerial insectivores, are experiencing steep population declines. Decreased insect abundance has been implicated as a potential cause of the decline. However, to determine if there is a guild-level effect of reduced insect abundance on swallows, research is needed to examine relationships between insect abundance and breeding success for multiple species. The goal of our study was two-fold. First, we determined if insect abundance during nestling rearing varied with breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
4
38
2
Order By: Relevance
“…Relying upon environmental sources of HUFA during the nestling period may make Tree Swallows and related species uniquely susceptible to phenological mismatches between their chicks' nutritional needs and the nutritional composition of prey items, perhaps even contributing to recent sustained population declines. Past studies focusing on total insect biomass have found only minimal effects of food availability on aerial insectivore breeding success (Dunn et al 2011;Nocera et al 2012;Imlay et al 2017). We also found that variation in terrestrial and total insect biomass, which increased steadily over the breeding season (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Relying upon environmental sources of HUFA during the nestling period may make Tree Swallows and related species uniquely susceptible to phenological mismatches between their chicks' nutritional needs and the nutritional composition of prey items, perhaps even contributing to recent sustained population declines. Past studies focusing on total insect biomass have found only minimal effects of food availability on aerial insectivore breeding success (Dunn et al 2011;Nocera et al 2012;Imlay et al 2017). We also found that variation in terrestrial and total insect biomass, which increased steadily over the breeding season (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…; Imlay et al . ). We also found that variation in terrestrial and total insect biomass, which increased steadily over the breeding season (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We also included nest-monitoring data for Tree Swallows from two long-term study sites on Kent Island, New Brunswick (1987-2006Wheelwright and Schultz 1994) and near Wolfville, Nova Scotia (1988-1990, 1994-2013Leonard and Horn 1996), and for all four species from several sites around Sackville, New Brunswick (2014-2016Saldanha 2016, Imlay et al 2017. MNRS volunteers in New Brunswick and Nova Scotia recorded data on the number of eggs and nestlings in the nests of all four species during one or more nest checks over the breeding season.…”
Section: Methodsmentioning
confidence: 99%